Implications of the empirical use of antimicrobials against uropathogens resistance found in a military hospital in Rio de Janeiro - Rodrigues, Daniele Caetano dos Santos; Rodrigues, Robson Carvalho de Abreu; Correal, Julio César Delgado; Abrantes, Jaime Antonio; Silva, Líllian Oliveira Pereira da; Nogueira, Joseli Maria da Rocha; Ignácio, Ana Cláudia de Paula Rosa (Seven Editora, 2023)
Bacterial resistance is a serious global public health problem, affecting different spheres of society, increasing hospital costs and reducing the patient’s chances of cure, since antimicrobials are no longer effective in the treatment of infections caused by such bacteria. Over the years, uropathogens, agents that cause urinary tract infections, have shown increasingly high rates of resistance, making it increasingly necessary to determine the susceptibility profile of such microorganisms. From this, the present study aimed to verify the antimicrobial resistance profile of the main uropathogens found in a military hospital in Rio de Janeiro. For the preparation of this study, all ethical principles were obeyed, being approved by the Research Ethics Committee of the Pedro Ernesto University Hospital, of the State University of Rio de Janeiro, where 825 positive urine culture reports were used, collected between March 2018 and March 2020. Among the main uropathogens identified, Escherichia coli stood out, totaling 72.9% of cases, followed by Klebsiella pneumoniae (13%), Proteus mirabilis (5.7%) and Acinetobacter baumannii (2.09%). Such bacteria can also cause the so- called asymptomatic bacteriuria, whose treatment is empirical and based on broad-spectrum antibiotics. By analyzing the susceptibility profile of these microorganisms, it was possible to identify a trend towards the growth of strains resistant to fluoroquinolones and carbapenems. The development of protocols for the rational use of antimicrobials can be a step forward for evidence-based clinical management. DOI:https://doi.org/10.56238/sevened2023.006-088